UTILIZATION OF OFFICE PAPER WASTE AS RAW MATERIAL FOR BRIQUETTES: A LITERATURE STUDY FROM AN ENVIRONMENTAL MANAGEMENT PERSPECTIVE - Rizky Ernando; Kelvin Dwiki Nugraha; Bernard Hasibuan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Office paper is a type of solid waste, and its volume continues to increase due to its widespread use in administrative activities. If not managed properly, this waste can cause environmental problems. One alternative use is as a raw material for briquettes, which can serve as a renewable energy source. This study aims to analyze the potential of office paper as a raw material for briquettes, evaluate the production process and quality of briquettes based on a literature review, and develop a sustainable waste management strategy. This study used a literature review method, collecting and analyzing various scientific literature, including journals, books, conference proceedings, and related publications. The results showed that waste paper has a high cellulose content, making it a potential raw material for briquettes. The briquette production process involves crushing the waste into pulp, mixing it with a binder, molding, and drying. According to several studies , waste paper briquettes have a calorific value between 3000-5000 kcal/g, a relatively low moisture content, and good combustion performance, but their ash content remains high compared to some other biomass. Briquette quality is influenced by factors such as paper type, material composition, binder type, pressing pressure, and drying process. From an environmental management perspective, the use of waste paper for coal briquette production aligns with the principles of a circular economy, the 3R principle (reduce, reuse, recycle), and the conversion of waste to energy. Therefore, the use of waste office paper as a raw material for coal briquettes effectively reduces waste volume while producing an alternative energy source that is economical, efficient, and environmentally friendly.